Tow placement studies for liquid composite moulding - Turner, Matthew Richard (1998)
This thesis describes the work undertaken developing techniques for the design and manufacture of continuous fibre preforms for liquid composite moulding. A prototype tow placement facility based on the roller placement of up to 5 tows onto a flat bed was developed. This was used to prepare preforms for 4 industrially based demonstrator components which were subsequently successfully moulded. In tests vibrational performance of parts so manufactured showed slight improvements in mechanical performance compared with those manufactured from conventional reinforcement.